Causes And Prevention Of Erosion In Urban Centres: A Case Of Okeotunu/Sanngo Area Of Ibadan City, Nigeria (2004)
The causes of erosion in the study area, Okeitunu/ Sanngo, were investigated via the geology and soil properties of the area, the state of the existing road network and the drainage system, and the solid waste management practice in the local government area. It was revealed that both natural and man made activities contributed to the erosion of the area. Topographical nature of Okeitunu and the inadequate stream channel, in addition to bad environmental sanitation practices, unchecked vegetative removal and lack of enlightenment on the part of the inhabitants on erosion problems are the key factors causing the degradation of the Okeitunu environment. Stabilization of the steep slope, rehabilitation of the existing bare roads and damaged drainage will abate the wearing away of the soil. In addition, the populace needs to be enlightened to know what it takes to initiate or aggravate erosion.